Comparative de novo Transcriptome Analysis of Two Cultivars With Contrasting Content of Oil and Fatty Acids During Kernel Development in Torreya grandis - Zhang, Chi; Liu, Haokai; Zhang, Hui; Dang, Wanyu; Zhou, Caihong; Zhang, Min (Frontiers in Plant Science, 2022)
Vegetable oil is indispensable and mainly characterized by the composition and content of fatty acids (FAs). As a commercial species of gymnosperm, Torreya grandis produces oil-rich nuts with high unsaturated fatty acids (UFAs) content in the mature kernels. In this study, two cultivars, T. grandis ‘Xifei’ and T. grandis ‘Dielsii’, with distinct oil content were employed to compare the profiles of FAs accumulation during kernel development. The growth rate of oil content was significantly different between ‘Xifei’ and ‘Dielsii’. Besides, the final oil content of ‘Xifei’ (52.87%) was significantly higher than that of 'Dielsii' (41.62%) at maturity. The significant differences of main FAs were observed at almost each kernel development between cultivars. C16:0, C18:1 and C20:3 FA exhibited different accumulation rules between cultivars. The content and initiation of accumulation of C20:3 FA were different between cultivars. To explore the molecular mechanism associated with different content of oil and FAs between two cultivars, de novo transcriptome of kernels was compared between ‘Xifei’ (high oil) and ‘Dielsii’ (low oil) at three stages of oil accumulation, respectively. Totally 142,213 unigenes were assembled and 16379 unigenes with a length over 1000nt were successfully annotated, including 139 unigenes related to FA biosynthesis, elongation and metabolism. Compared with ‘Dielsii’, totally 1476, 2140 and 1145 DEGs were up-regulated in ‘Xifei’ at the stage of initiative, the rapid rise and the stationary oil accumulation, respectively; the number of down-regulated DEGs reached 913, 1245 and 904, respectively. Relative expressions of 11 DEGs involved in FAs biosynthesis and metabolism were confirmed by RT-qPCR. Abundant differentially expressed transcription factors (DETFs) and pathway DEGs were correlated to oil and FAs according to Pearson's correlation analysis between transcriptome and metabolites (oil and FAs), suggesting their contributions to the differential oil and FAs between the two cultivars during kernel development of T. grandis. To conclude, our findings can provide novel insights into the developmental differences in metabolites and de novo transcriptome correlated to lipid accumulation and FA synthesis of kernels between cultivars with contrasting oil deposits and demystify the regulatory mechanism of high oil accumulation in T. grandis.